Accuracy and Clinical Utility Evaluation of Surgical Techniques for the Management of Kidney Stones. Efficacy and Complications - Shahjehan, Maaz Bin Altaf, Syed Ameroon Shah, Maham Arooj Zaidi, Khaid Islam, Faheem Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: 200 patients at the Department of Urology, IKD Peshawar, were evaluated for their accuracy and clinical value in treating kidney stones. The characteristics of the patient population, surgical management techniques, therapeutic effectiveness, and postoperative complications were evaluated. Results demonstrated that the majority of surgical procedures had favorable results. Infection was the most typical postoperative consequence in 4% of the patients. These findings imply that surgical procedures to treat kidney stones are an effective alternative with excellent therapeutic value and a low risk of complications. More study is required to validate and build upon these results in a larger patient population. Objectives: 1 Assess the effectiveness of surgical methods for treating kidney stones in 200 patients. 2 Evaluate the clinical efficacy of various surgical kidney stone therapies 3 Examine the effectiveness of various surgical kidney stone therapies. 4 Quantify the frequency of complications after surgery related to removing kidney stones. Methods: This retrospective study assessed the precision and clinical applicability of surgical procedures for treating kidney stones in 200 patients treated at the Department of Urology, IKD Peshawar, from January 2021 to January 2022. Patient demographics, surgical management techniques, treatment effectiveness, and postoperative complications were among the data examined. Results: The findings of the Study demonstrated that the majority of patients who had surgical procedures experienced favorable outcomes. Infection was the most typical postoperative consequence in 4% of the patients. Although the frequency was low, minor problems were also seen, including bleeding and blood in the urine. Conclusion: The findings of this Study indicate that adopting surgical procedures with excellent clinical value and a relatively low risk of complications is a practical choice for treating kidney stones. More study is required to validate and build upon these results in a larger patient population. Keywords: Kidney Stones, Surgical Treatment, Accuracy, Clinical Utility, Efficacy, Complications